Pengaruh pemberian kompleks kalsium dan ampas jamu fitobiotik dalam pakan terhadap profil darah itik petelur mojosari (Anas javanica) periode layer - Muhammad A. Y. Harahap; Cindy A. Damayanti; Syahputra Wibowo; Muhammad H. Natsir; Osfar Sjofjan (Jurnal Ilmu Peternakan dan Veteriner Tropis, 2023)
The use of Natural Growth Promoters (NGP) in phytobiotics as a substitute for Antibiotics Growth Promoters (AGP) is being intensively used by utilizing Indonesian herbal medicinal plants in the form of herbal pulp to spur growth, increase feed efficiency and productivity and suppress feed conversion. This study aimed to obtain information about the complex of calcium and herbal pulp in the feed ration of ducks to blood profile (hematocrit, haemoglobin, erythrocytes, leukocytes and leukocyte differentiation (lymphocytes, heterophile, monocytes, eosinophils, basophils and H / L ratios)). This study used 120 24-week-old mojosari laying ducks with cages randomly divided into 6 treatments with 4 tests (5 mojosari ducks each). The treatment in this study consisted of: P0 (basal feed without antibiotics), P1 (basal feed + antibiotics (zinc bacitracin) 0.1%), P2 (basal feed + phytobiotic calcium 0.25%), P3 (basal feed + phytobiotic calcium 0.5%), P4 (basal feed + phytobiotic calcium 0.75%) and P5 (basalt feed + calcium phytobiotics 1%). Treatment feeding for 60 days. Samples are collected at the end of the study period for a complete blood test. Statistical data analysis using one-way ANOVA, if it has a real effect, will be followed by Duncan's further test with data visualization using the Prism application. The results showed that the complex administration of calcium and phytobiotic herbal pulp in the feed did not significantly affect the value of hematocrit, haemoglobin, erythrocytes, leukocytes, and leukocyte differentiation compared to the control (P>0.05). Based on the study results, it was concluded that the administration of calcium pulp of phytobiotic herbs in feed with different levels for 60 days did not affect the blood profile of mojosari laying ducks, but the condition was still in normal physiology.